Pengaruh Literasi Keuangan, Motivasi Investasi, dan Modal Minimal Investasi Terhadap Minat Berinvestasi Gen Z pada Aplikasi Bibit - Kartika Sukmawati (Universitas 17 Agustus 1945, 2023)
The aim of this research is to analyze the influence of financial literacy, investment motivation, and minimum investment capital on Gen Z's investment interest in the Bibit application. The analysis method in this research uses quantitative primary data, the test stages carried out are: validity test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test, and coefficient of determination test (R2). The data used in this research used a questionnaire instrument, and valid data was collected from 100 respondents. The sampling method in this research is non-probability sampling with a purposive sampling technique. The testing tool used was SPSS version 23. The results showed that investment motivation and minimum investment capital had a partially significant positive effect on Gen Z's interest in investing in the Bibit application, while financial literacy had a partially significant negative effect on Gen Z's investment interest in the Bibit application. Financial literacy, investment motivation, and minimum investment capital simultaneously have a positive effect on Gen Z's interest in investing in the Bibit application and the most dominant variable in investment interest is investment motivation.